High School Students' Mathematical Skills in Addressing Minimum Competency Assessment Problems using Working Backward Strategy - Siti Inganah; Annisa Nurina Vidyastuti; Retno Wahyu Arian Sah (STAI Hubbulwathan Duri, 2023)
Strategy problem-solving is a technique or method for finding answers to problems. Students' different maths skills can affect how they use and figure out ways to solve problems. This type of research is descriptive and uses a qualitative approach. Its goal is to find out and analyse how the backward working strategy is used to solve the Minimum Competency Assessment (AKM) questions on the spatial structure in terms of students' maths skills. After giving people a test of their maths skills and giving them problems to solve, they were interviewed. Students with high, medium, and low maths skills are taking part in this study. Data analysis used is data reduction, data presentation, and data retrieval. The results were based on the six students who participated in the research. Students could use Polya problem-solving steps with high and moderate maths skills, but they didn't work well for students with low maths skills. Working backwards is not a method used by everyone. The first student with good maths skills can use the strategy of working backwards from the correct answer. The second student with good maths skills can't do that. The backward plan makes few mistakes. The answer is wrong for the first student with average maths skills because they do not have a backwards strategy. The second student with average maths skills can use the backward working strategy, but they make a lot of mistakes. The first and second students with low maths have not used the backward working strategy, even though the mathematically able student has. The first low can show that the statement is true.